Calcium‐Ion Batteries: Stable and High‐Power Calcium‐Ion Batteries Enabled by Calcium Intercalation into Graphite (Adv. Mater. 4/2020). Issue 4 (27th January 2020) - Park, Jooha; Xu, Zheng‐Long; Yoon, Gabin; Park, Sung Kwan; Wang, Jiang; Hyun, Hyejeong; Park, Hyeokjun; Lim, Jongwoo; Ko, Yoon‐Joo; Yun, Young Soo; Kang, Kisuk
Abstract : Graphite is realized as a reliable anode material for calcium‐ion batteries by Kisuk Kang and co‐workers, as described in article number 1904411 . By selecting a suitable dimethylacetamide‐based electrolyte, Ca ions (de)intercalate into graphite at room temperature with large Ca‐storage capacities, remarkable reversibility, and exceptionally high rate capability. This work provides a promising pathway toward the realization of high‐power and long‐lasting calcium‐ion batteries.